The commonality between the notion of singularity within community and its reflections in the Islamic culture with early Islamic practices - Akbaba, Yunus (İstanbul Bilgi Üniversitesi, 2010)
Bu çalışma tekil yaşamın ve tekil deneyimlerin hem teorik hem de pratik düzeyde sorgulanmasından oluşmaktadır. İlk bölümde, Batı düşüncesindeki epistemolojik sürecin bir ürünü olan toplum içinde birey(sel)leşmesi gereken bir varlık olarak kavranan insanı cemaatin içindeki tekillik olarak sunan bu çalışma daha sonraki bölümlerde ise tekil insanın `öteki' ile olan konumundan yola çıkarak yeni bir ilişkisellik ve cemaat durumunu ortaya koymaktadır. Son olarak bu sorgulamanın bir yansıması olarak İslami kültürün bel kemiğini oluşturan erken islam dönemindeki olaylar incelenmektedir. Bu olaylar karşılaştırmalı bir şekilde modern yaşam anlayışı ile arasındaki bağları ve farkları da göz önüne çıkarmaktadır.

This thesis attempts to constitute a questioning about both theory and practice of singularity experiences. In general terms, this work consists of two major parts. The former, human beings are defined as singular entities rejecting the notions of individual and society as the products of epistemological process of Western thought. Singular beings qualifications within the community and its inclination towards the other constitutes the grand pillar of this work. The latter is the very reflections of that philosophical investigation in the Islamic culture which is best experienced in the early Islamic practices. In that sense, the features and institutions with experiences of people in that community are analyzed in a comparative manner with modern understanding of life.
Cemaat içindeki tekillik kavramının erken dönem İslam pratikleriyle beraber İslam kültüründeki yansımaları